Efektivitas Metode Yanbu’a Dalam Meningkatkan Kualitas Membaca Al-Qur’an Santri Pondok Pesantren Ihyaul Ulum - Maghfiroh, Lailatul; Thoharun, Muhammad; Fauziyah, Nina Rohmatul (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2022)
Al-Qur'an is the word of Allah revealed to Muhammad SAW through the angel Gabriel with lafadz-lafadz in Arabic and got a reward for those who read it so that Muslims can be proficient in reading the Al-Qur'an. Still, increasing technology is not supported by improving the quality of Reciting Al-Qur'an. One of the Al-Qur'an learning methods that is used as a solution to overcome this problem is the Yanbu'a method. A practical and effective way that facilitates fluency in reading the Koran, while the formulation of this problem is the effectiveness of the Yanbu'a method in improving the reading quality of the Koran for Islamic boarding school students Ihyaul Ulum Gilang Babat. The study results can be seen from the average pretest score of 62.87 and posttest score of 78.60. so that the average increase value is 15.73. in KKM it increased completeness. Before the Yanbu'a method, there were 10 students with a percentage of 33.3%, while after Yanbu'a there were 24 students with completion criteria with a rate of 80%. It can be concluded that the Yanbu'a method proved effective in improving the quality of reading the Koran for students at the Ihyaul Ulum Gilang Babat Islamic Boarding School